Comparison of chloroprocaine and chloroprocaine with clonidine in spinal anaesthesia: A prospective study, double-blind randomised trial - Aslam K M; Asif P Mammutty; Daber Pareed; Sunny Alex; Vijish Venugopal (International Journal of Health and Clinical Research, 2022)
Background and Aims: Clonidine improves quality of spinal anaesthesia as an adjuvant with bupivacaine and ropivacaine, but has not been studied much in combination with preservative-free 2-chloroprocaine, hence this study. Methods: This prospective randomised control trial was conducted in 60 adult male patients of age 18-60 years undergoing urological surgeries of short duration (<40 minutes). Patients were randomly assigned into two groups: Group A (n=30), patients who received intrathecal injection of 2-chloroprocaine and Group B (n=30), patients who received intrathecal injection of 2-chloroprocaine with 30μg of clonidine. The primary aim of our study was to compare isobaric 1% 2-chloroprocaine and 1% 2-chloroprocaine with 30μg of clonidine in terms of onset and duration of motor block, onset and duration of sensory block, time for 2 segment regression of sensory block and peak block height. Statistical analysis was done using SPSS version 20.0. Quantitative data was analysed by student’s ‘t’ test and qualitative data by Chi-square test. Results: Onset of sensory blockade was faster and peak block height was higher for Group B. There was no statistically significant difference in the onset of motor blockade and time of 2 segment regression between the two groups. The total duration of sensory and motor block was longer in Group B compared to Group A and mean time for first request of analgesic was longer in Group B compared to Group A. There was no statistically significant difference in the heart rate and mean arterial pressure between the groups at various time intervals. There was no incidence of hypotension, bradycardia or post spinal head ache in the two groups. Conclusion: Addition of 30μg of Clonidine to 4ml of 1% Chloroprocaine intrathecally enhances onset and duration of sensory and motor blockade in urological surgeries of short duration without significant difference in the hemodynamic parameters and side effects compared to Chloroprocaine alone.